A theoretical framework for a structuration model of social issues in software development in information systems - Loureiro-Koechlin, C (John Wiley & Sons, Ltd., 2008)
This study looks at how human and social issues affect software developers' work and the software they produce. It focuses on the development of software to support information systems, and therefore positions software development as an activity within Information Systems Development. Although some research in IS and software development address human and social issues they do so by considering either business organisations or software development environments separately but do not connect both contexts together. This research tries to build this connection through a model of social issues in software development. The model was generated from data collected from an interpretive online ethnography of virtual communities of software developers. The model of social issues complements Orlikowski's structurational model of enactment of technologies-in-practice and suggests that human and social issues that affect the production of software emerge from three different contexts: software development environment, software development practices and complex business organisations.